The travel of Nebuchadnezzar`s army in ‘Judith’ and its relevance to the Jewish literature of the Hellenistic Age - Passuello, Victor (Romanitas - Revista de Estudos Grecolatinos, 2021)
The Book of Judith (134-76 B.C.E), which belongs the apocrypha literature of the Old Testament, written in koine Greek, has received a great attention from the scholars of the Second Temple Period due to the role of the heroin Judith in its narrative. The book borrows its title from the heroin Judith and its composed by sixteen chapters. However, the story of Judith begins only in the eighth chapter. This fact raised a lot of questions about the meaning of the first chapters of the book of Judith. Therefore, we will propose that the first half of the book of Judith can be classified, particularly the fictitious travel of Nebuchadnezzar´s army, as a critical and fictitious global history of the great ancient empires which subjugated the Jews.
Keywords: Judith; Global literature; Jews; Ancient Empires